Zoogeographical characteristics of Coleoptera, Carabidae of the Steppe areas of the Southeast of Russia and Northeast of Azerbaijan - G. M. Abdurakhmanov; S. M. Klicheva (Юг России: экология, развитие, 2015)
The features of the structure and of the areas of Coleoptera, Carabidae of the region are given in the work